Socio-economic relations between India and China: understanding and examining the significance of trade. (7th March 2023) - Kolte, Ashutosh; Sangvikar, Balkrishan; Pawar, Avinash; Lirong, Qu
In recent years, two giant countries China and India, are taking attention from the world due to fast economic developments. China is the first-largest economy and India is the third-largest economy in terms of gross domestic product (GDP) on purchasing power parity (PPP) basis. China has a dominating position in international trade, whereas India's trade has shown sluggish growth. In this research, we analysed socio-economic relations between India and China and deliberated to understand socio-economic relations between both the countries, mainly emphasising on trade. We used data such as GDP trends, bilateral trade trends, relative competitive advantage index, and the complementarity index to explain the trade complementary of bilateral trade and reasons for trade confliction between India and China. It is found that cooperation, competition, and confliction coexist in the socio-economic relations, and that potential economic collaborations are possible between India and China to bring a bright future for both countries.